Brain‐wide versus genome‐wide vulnerability biomarkers for severe mental illnesses. Issue 16 (30th August 2022) - Kochunov, Peter; Ma, Yizhou; Hatch, Kathryn S.; Jahanshad, Neda; Thompson, Paul M.; Adhikari, Bhim M.; Bruce, Heather; Van der vaart, Andrew; Goldwaser, Eric L.; Sotiras, Aris; Kvarta, Mark D.; Ma, Tianzhou; et al.
Abstract: Severe mental illnesses (SMI), including major depressive (MDD), bipolar (BD), and schizophrenia spectrum (SSD) disorders have multifactorial risk factors and capturing their complex etiopathophysiology in an individual remains challenging. Regional vulnerability index (RVI) was used to measure individual's brain‐wide similarity to the expected SMI patterns derived from meta‐analytical studies. It is analogous to polygenic risk scores (PRS) that measure individual's similarity to genome‐wide patterns in SMI. We hypothesized that RVI is an intermediary phenotype between genome and symptoms and is sensitive to both genetic and environmental risks for SMI. UK Biobank sample of N  = 17, 053/19, 265 M/F (age = 64.8 ± 7.4 years) and an independent sample of SSD patients and controls ( N  = 115/111 M/F, age = 35.2 ± 13.4) were used to test this hypothesis. UKBB participants with MDD had significantly higher RVI‐MDD (Cohen's d  = 0.20, p  = 1 × 10 −23 ) and PRS‐MDD ( d  = 0.17, p  = 1 × 10 −15 ) than nonpsychiatric controls. UKBB participants with BD and SSD showed significant elevation in the respective RVIs ( d  = 0.65 and 0.60; p  = 3 × 10 −5 and .009, respectively) and PRS ( d  = 0.57 and 1.34; p  = .002 and .002, respectively). Elevated RVI‐SSD were replicated in an independent sample ( d  = 0.53, p  = 5 × 10 −5 ). RVI‐MDD and RVI‐SSD but not RVI‐BD were associated with childhood adversity ( p  < .01). In nonpsychiatric controls, elevation in RVI and PRS were associated with lower cognitive performance ( p  < 10 −5 ) in six out of seven domains and showed specificity with disorder‐associated deficits. In summary, the RVI is a novel brain index for SMI and shows similar or better specificity for SMI than PRS, and together they may complement each other in the efforts to characterize the genomic to brain level risks for SMI. Abstract : Capturing an individual's risk of severe mental illnesses (SMI) is complicated by complex etiopathophysiology and multiple factors. We propose a regional vulnerability index (RVI) to quantify an individual's brain‐wide similarity to expected SMI patterns, analogous to polygenic risk scores (PRS) that measure an individual's similarity to SMI genome‐wide patterns. Using a large imaging dataset from the UK BioBank, we show that RVI is a novel brain index for SMI and shows similar or better specificity for SMI than PRS, which together complement each other to characterize the genomic to brain level risks of severe mental illness.